Photovoltaic Forced Convection Greenhouse Solar Dryer with an Integrated Vertical Solar Collector for Mango Drying - Simate, Isaac N.; Simukonda, Kondwani (European Journal of Applied Sciences, 2022)
The design and experimentation of a Photovoltaic forced convection greenhouse solar dryer with a vertical solar collector incorporated inside the drying chamber for mango drying is presented. The integrated vertical solar collector combined the features of a south wall and a solar air heater to capture solar radiation that escapes through the south wall (north wall for the northern hemisphere) and heat the air before it enters the drying chamber. Mango drying experiments were carried out to ascertain the performance of the dryer. The solar radiation at the beginning of the experiments at 08:30 hours was 525.1 W/m2, reaching a maximum of 1,133.0 W/m2 shortly after midday and decreasing to 492.4 W/m2 at 16:30 hours when the experiments were stopped. The ambient temperature and relative humidity ranged from 28.4 ⁰C to 36.4 ⁰C and 19.9% to 37.8%, respectively. Under these conditions, the air temperature inside the drying chamber was on average 14.7 ⁰C above ambient, resulting in high drying rates such that the mango reached the moisture content of 13.7% wet basis after 7.5 hours of drying. The incorporation of a vertical solar collector inside the drying chamber helped, through storing heat in its mass, stabilise the drying chamber air temperature and made the forced convection dryer more compact thereby reducing usage of the space outside the dryer and making it available for other operations.